Contribution of Wages and Production in the Personal Care Industry to the Growth of the Composite Stock Price Index in Indonesia 2010-2023 - Goestjahjanti, Francisca Sestri (Politeknik Negeri Semarang, 2025)
The purpose of this research is to analyze and discuss the impact of the magnitude of the influence of the wages and the production factors on the Indeks Harga Saham Gabungan (IHSG) of the personal care industry in Indonesia during 2010 up to 2023. The study use the expalantory research method, which is related to the hypothesis test between the affecting variables against predicted variables in the scheme of a model. The analysis technique in this research is linear regression for processing the secondary data and the time series type for 14 years. This study provides evidence of the hypotheses is stated in Model 1, there is a significant effect of the Wages variable on the IHSG of the consumtion In Model 2, there is a significant impact between the Production on the IHSG of the consumtion industry. Simultaneously shown in Model no. 3, there is a significant influence between the Wages and the Production on the IHSG of the personal care industry in Indonesia, with a contribution of 90,50 %. Indek Harga Saham Gabungan (IHSG) is one of the indices for measuring investment growth, so the Financial Services Authority (OJK) must monitor it more intensively so that it continues to grow and attract investors to invest their capital in Indonesia.